Repair and maintenance cost of combine harvester in rice harvesting at Kedah / Mohammad Izwan Ismail - Ismail, Mohammad Izwan (Faculty of Plantation and Agrotechnology, 2015)
A research was conducted to investigating the factor that effect repair and maintenance cost of combine harvester. Combine harvester is use to overcome shortage of manpower in agriculture sector. Repair and maintenance cost is the main factor in order to select a new or second hand combine harvester because the capacity or age of the machine may increase the cost of repair and maintenance. Common model of combine harvester that is mainly use in Malaysia is New Holland. The research was conducted in Langkawi and Kota Setar district. This research is significant for the conductor or owner to decide the best combine harvester before purchasing. The combine harvester with several ability and durability that can enhance the efficiency of the combine harvester in harvesting operation . Cross section survey that is use to collect the data and regression and correlation matrix is the data interpreted result in the research model. The distribution of critical parts have changed during repair and maintenance cost activities are ground speed vari-drive (24%), shaft tire (18%) and grain elevator drive (9%), for the maintenance in off season the part normally changed are wheel, conveyor belt and pump bush track (10%), Soucy track (9%), and, straw walker and header (8%). Combine harvester need to be repair and maintenance after usage in between 60I to 900 hours in seasons. The owner or farmer need to repair and maintained the combine harvester to reduce the factor that enhance combine harvester breakdown. This problem needs to overcome to reduce the losses to owner of combine harvester. Machinery cost is the secondary highest cost after own the land.